Institutional investors vs retail investors: Are psychological biases equally applicable to investor divides in Malaysia? - Jaiyeoba, Haruna Babatunde; Abdullah, Moha Asri; Ibrahim, Khairunisah (Emerald Publishing Limited, 2020)
Purpose – Guided by several pioneered studies, the purpose of this paper is to comprehensively investigate the investment behaviours of Malaysian retail and institutional investors in an attempt to identify whether the influence of psychological biases is equally applicable to investor divides. Design/methodology/approach – The researchers have adopted a quantitative research design by way of survey methodology to obtain data from institutional and retail investors in Malaysia. In addition, the authors have mainly employed second-order measurement invariance analysis to uncover the difference across investor divides. Findings – The tests of measurement invariance at the model level indicate an insignificant difference between institutional investors and retail investors. The post hoc test (at the path level) reveals that institutional and retail investors are similar with respect to representative heuristic, overconfidence bias and anchoring bias; though the results also show that they are different with respect to religious bias and herding bias. Research limitations/implications – Based on the findings of this study, it is generally not logical to assume that institutional investors completely behave rational during investment decisions. Besides, future researchers are called upon to directly compare the investment decisions of institutional and retail investors with respect to whether the influence of psychological biases is equally applicable to them, particularly on the investigated psychological biases and other psychological biases that are not covered in this study. Originality/value – This study has offered insight into whether the influence of psychological biases is equally applicable to institutional and retail investors in Malaysia using second-order measurement invariance analysis. This study is unique in context and the approach it has adopted.